On the dynamic multiple intelligence informed personalization of the learning environment - Kelly, Declan (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2006)
Educational research informs us "one size does not fit all" (Reigeluth, 1996). It states that learners, reflecting individual traits, possess different learning characteristics, process and represent knowledge in different ways, prefer to use different type of resources and exhibit consistent observable patterns of behaviour (Riding & Rayner, 1998). Research also suggests that it is possible to diagnose a student's learning traits and that some students learn more effectively when instruction is adapted to the way they learn (Rasmussen, 1998).
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin